Pilot Solar Thermal Power Plant Station in Southwest Louisiana - Terrence Chambers; Jonathan R Raush; G.H. Massiha (Institute of Advanced Engineering and Science, 2013)
Solar thermal plants are basically power plants that generate electricity from high-temperature heat. The difference between them and conventional power plants is that instead of deriving energy from gas, coal or oil, the sun provides the energy that drives the turbines. In this paper we will give a brief demonstration of solar thermal power and different system designs of solar thermal power plants. Then we will see the feasibility of implementing solar power plants in Louisiana which currently depends mostly on its conventional power plants which use traditional fuels such as gas, oil, and coal. This study was a part of a proposal that was funded by the US the Department of Energy to construct solar thermal plant near Lafayette, Louisiana. The power plant is currently under the construction and it will be completed by Summer of 2013.